2019
DOI: 10.3390/f10080667
|View full text |Cite
|
Sign up to set email alerts
|

Ground-Dwelling Arthropod Community Responses to Recent and Repeated Wildfires in Conifer Forests of Northern New Mexico, USA

Abstract: The increasing frequency and severity of wildfires in semi-arid conifer forests as a result of global change pressures has raised concern over potential impacts on biodiversity. Ground-dwelling arthropod communities represent a substantial portion of diversity in conifer forests, and could be particularly impacted by wildfires. In addition to direct mortality, wildfires can affect ground-dwelling arthropods by altering understory characteristics and associated deterministic community assembly processes (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Among the relatively few studies that have explicitly used a mechanistic approach, generalities have been elusive because anthropogenic drivers influence metacommunity functioning in multiple, often interactive, ways. [96][97][98][99][100] This is corroborated by meta-analyses showing that responses after disturbance are highly variable, and depend, among other things, on the type of disturbance, habitat, and trophic role. [101][102][103] Therefore, to understand global change effects on the conservation of populations and biodiversity, we need to understand how each metacommunity process, alone or in concert, is altered by these global change drivers.…”
Section: Pollutionmentioning
confidence: 72%
See 1 more Smart Citation
“…Among the relatively few studies that have explicitly used a mechanistic approach, generalities have been elusive because anthropogenic drivers influence metacommunity functioning in multiple, often interactive, ways. [96][97][98][99][100] This is corroborated by meta-analyses showing that responses after disturbance are highly variable, and depend, among other things, on the type of disturbance, habitat, and trophic role. [101][102][103] Therefore, to understand global change effects on the conservation of populations and biodiversity, we need to understand how each metacommunity process, alone or in concert, is altered by these global change drivers.…”
Section: Pollutionmentioning
confidence: 72%
“…However, evidence for the impact of global change on metacommunity processes and functioning has been largely circumstantial. Among the relatively few studies that have explicitly used a mechanistic approach, generalities have been elusive because anthropogenic drivers influence metacommunity functioning in multiple, often interactive, ways 96–100 . This is corroborated by meta‐analyses showing that responses after disturbance are highly variable, and depend, among other things, on the type of disturbance, habitat, and trophic role 101–103 .…”
Section: Anthropogenic Drivers Altering Metacommunity Processesmentioning
confidence: 99%
“…Growth ultimately is contingent on the availability of food resources, however, which for boreal toads includes primarily arthropods, principally ants (Formicidae), beetles (Coleoptera), and spiders (Bull, 2006; Bull & Hayes, 2009; Campbell, 1970). Wildfire can increase the diversity and abundance of arthropods and other invertebrates (Bess et al, 2002; Buddle et al, 2006; Ferrenberg et al, 2019; Jackson et al, 2012), and high‐severity fires can result in an extended “fire pulse” characterized by a flux of invertebrate prey to aquatic and terrestrial habitats (Harris et al, 2018; Malison & Baxter, 2010; Silins et al, 2014). Post‐fire increases in prey availability therefore may have stimulated the growth of boreal toads between 2019 and 2020 at burned sites in our study area.…”
Section: Discussionmentioning
confidence: 99%
“…Dispersal capacity of species contributes to processes of community assembly at landscape and local scales, including patterns of probabilistic dispersal and recolonization following natural and anthropogenic disturbances. Studies of arthropod community assembly have often found that a combination of stochastic (neutralbased) and deterministic (niche-based) processes shape patterns of assembly (Thompson and Townsend 2006, Farnon Ellwood et al 2009, Rominger et al 2009, Ferrenberg et al 2019, Perry et al 2020), but disturbances can mediate the relative importance of these mechanisms. For example, following tree mortality caused by bark beetles, the relative importance of deterministic processes related to plant and soil habitat characteristics increased in strength for grounddwelling arthropods, while stochastic processes related to dispersal limitations increased for soildwelling arthropods (Ferrenberg et al 2016).…”
Section: Discussionmentioning
confidence: 99%